Optimizing the operating conditions of gold elution and electrowinning for Tau Lekoa stream at Kopanang gold plant - Lunga, Alfred Lodi (My University, 2008)
The final gold product of Tau Lekoa mine has a low fineness. This is caused by high concentration of bases metals in the reefs. Some of these base metals together with gold are leached with cyanide and are loaded into carbon. If not adequately controlled, they may elute with gold and contaminate the final product in the electrowinning process. Based on the understanding of the kinetics of the elution, four parameters, namely temperature, flow rate, free caustic soda concentration and cyanide strength, were evaluated first for the elution process. Experimental runs on the plant scale did prove that the first three parameters are the predominant parameters that maintain base metals in the carbon during the elution and therefore assist in the improvement of the fineness of the final product. Recommendations were made to change the operating conditions and the fineness of the gold did improve from 80% to 84 %. In addition, a thermodynamic model that took to consideration the competition of gold and nickel was developed for the electrowinning process. This model showed that the deposition of gold and nickel during the electrowinning was dependant of their concentrations and temperature. The single pass efficiencies and the deposition rates were also tracked during the experimental. Based on the finding on the reduction of electrowinning time, the fineness of the final product was improved from 84% to 85%. As the refining cost depends on the fineness of gold, the improved fineness means that the gold content in the bullion is increased and the impurities are decreased, therefore, the refining cost will decrease as lower penalty costs are charged for the treatment of the bullion with high fineness. The recommendations of the changes have been implemented permanently and these did show permanent improvement of the fineness.
Keywords: Gold; Metallurgy